Neural network based detection of voice disorders using energy spectrum and equal-loudness contours - Murugesa Pandian, Paulraj, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Sivanandam, S. N.; Muthusamy, Hariharan, Dr. (Universiti Teknologi MARA (UiTM), 2011)
Organized by Universiti Teknologi MARA (UiTM) Shah Alam, 7th - 9th March 2008 at Royale Bintang Hotel, Kuala Lumpur, Malaysia.